Pitch detection base on EMD and the second spectrum - Jingfang Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A new method for pitch detection of secondary spectrum is designed in the paper, the noisy speech oval (Elliptic Filter, EF) band-pass filter is designed first in this method, and then  the experience mode Decomposition(EMD)of Hilbert-Huang transform (HHT) is used to decompose the signal into a finite number of intrinsic mode functions (IMF), and IMF components of different scales are associated with the decomposition of the signal before calculation, the maximum of two modes associated (IMF) synthetic pitch signal detection is taken. Experimental results show that the method could be better than the traditional autocorrelation method, and cepstrum method has better results, especially with voicing obvious segment features, there is better performance of pitch detection in noisy speech, signal to noise ratio(SNR) also has good robustness in the lower sound environment. http://dx.doi.org/10.11591/telkomnika.v12i12.6482